PECULIARITIES OF FORMATION OF A REGIONAL SYSTEM OF EDUCATIONAL QUALITY CONTROL - N.F. EFREMOFA (Advanced Engineering Research, 2009)
Scientific and practical foundations of formation and functioning of regional systems of educational quality control as constituent parts of the national system are reviewed. The experience of the Rostov Region in independent evaluation and informational support of the data pertaining to quality of regional education and important to improvement of effectiveness of educational systems and processes control is presented.